Determination of Effectiveness of combined Biological and Physicochemical Treatment of Vinasse - Juma, Juma; Said, Mahir; Msuya, Neema (Tanzania Journal of Engineering and Technology, 2023)
Combined biological and Physicochemical treatment method was used to treat vinasse using microorganisms (Aspergillus niger (fungi) and Bacillus subtilis (bacteria)), coagulants (aluminium sulphate (Al2(SO4)3) and iron III chlorides (FeCl3)) and followed by filtration. Three factors; coagulant type, type of microorganism and coagulant concentration was analysed using full factorial design (2n) with replication, on their percentage removal of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS) and turbidity. Pareto chart and regression analysis with a 95% confidence interval (5% significant level) were used to analyse the results using MINITAB 22 (current version). Initially, the vinasse had (COD), (BOD), (TSS), and turbidity of 10240 mg/ „“, 5340 mg/ „“, 400 mg/ „“, and 1980 NTU, respectively, and a pH of 5.68. COD, BOD, TSS, and turbidity were reduced by 99.5%, 99.7%, 99.7%, and 93.7%, respectively, after the treatment, while pH was raised to 7.5, which is neutral. Using Bacillus subtilis and aluminium sulphate, the combined biological and physicochemical process produced good results for the treatment of vinasse. Keywords: Combined Biological and Physicochemical Treatment, flocculants, Vinasse, Pareto chart, Bacillus subtilis Combined biological and Physicochemical treatment method was used to treat vinasse using microorganisms (Aspergillus niger (fungi) and Bacillus subtilis (bacteria)), coagulants (aluminium sulphate (Al2(SO4)3) and iron III chlorides (FeCl3)) and followed by filtration. Three factors; coagulant type, type of microorganism and coagulant concentration was analysed using full factorial design (2n) with replication, on their percentage removal of Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS) and turbidity. Pareto chart and regression analysis with a 95% confidence interval (5% significant level) were used to analyse the results using MINITAB 22 (current version). Initially, the vinasse had (COD), (BOD), (TSS), and turbidity of 10240 mg/ „“, 5340 mg/ „“, 400 mg/ „“, and 1980 NTU, respectively, and a pH of 5.68. COD, BOD, TSS, and turbidity were reduced by 99.5%, 99.7%, 99.7%, and 93.7%, respectively, after the treatment, while pH was raised to 7.5, which is neutral. Using Bacillus subtilis and aluminium sulphate, the combined biological and physicochemical process produced good results for the treatment of vinasse.